An oscillating dynamic model of collective cells in a monolayer. (March 2018) - Lin, Shao-Zhen; Xue, Shi-Lei; Li, Bo; Feng, Xi-Qiao
Highlights: Spontaneous oscillation of collective cells induced by Hopf bifurcation. Oscillating cytodynamic model integrating coupled chemical and mechanical mechanisms. Chemomechanical feedback between RhoA effector signaling pathway and cell deformation. External forces modulate the polarization and oscillation intensity of cells. Abstract: Periodic oscillations of collective cells occur in the morphogenesis and organogenesis of various tissues and organs. In this paper, an oscillating cytodynamic model is presented by integrating the chemomechanical interplay between the RhoA effector signaling pathway and cell deformation. We show that both an isolated cell and a cell aggregate can undergo spontaneous oscillations as a result of Hopf bifurcation, upon which the system evolves into a limit cycle of chemomechanical oscillations. The dynamic characteristics are tailored by the mechanical properties of cells (e.g., elasticity, contractility, and intercellular tension) and the chemical reactions involved in the RhoA effector signaling pathway. External forces are found to modulate the oscillation intensity of collective cells in the monolayer and to polarize their oscillations along the direction of external tension. The proposed cytodynamic model can recapitulate the prominent features of cell oscillations observed in a variety of experiments, including both isolated cells (e.g., spreading mouse embryonic fibroblasts, migrating amoeboid cells, and suspending 3T3 fibroblasts) and multicellular systems (e.g., Drosophila embryogenesis and oogenesis). Graphical abstract: Image, graphical abstract